Hip sonography in Switzerland - Beat Dubs (Exploration of Musculoskeletal Diseases)
The diagnosis of hip dysplasia has developed very differently in different countries over the last few decades. The development and current situation in Switzerland is described in this paper. In the meantime, early diagnosis by means of Graf hip sonography, corresponding to screening, has been established, although it varies from region to region. The training system for examiners is also clearly regulated. The massive reduction in costly treatments and operations documents the success of the efforts made in Switzerland.